Properties and application of electrochemically anodized Ta2O5 nanostructures: a review / Nur Lili Suraya Ngadiman ... [et al.] - Ngadiman, Nur Lili Suraya; Abdul Rani, Rozina; Makhsin, Siti Rabizah; Ayub, Muhammad Azmi; Aryani, Dharma; Zoolfakar, Ahmad Sabirin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
Anodization is one of the simplest synthesis methods that can be employed to generate generous nanostructures metal oxide. Knowing the potential of anodized Tantalum Pentoxide (Ta2O5) to form the desired nanostructure which is capable to produce outstanding performance, the elements and factors influence properties enhancement were gathered. The effect of parameter variation during anodization such as electrolyte composition, voltage variation, and anodization duration was evaluated to inspect the nanostructure formed. The results generated the differences in properties of nanostructures. Characterization methods such as field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), Transmission electron microscopy (TEM), Atomic force microscopy (AFM), and X-ray electron spectroscopy (XPS) were used to investigate the structural, electrical, chemical, optical, biological and mechanical properties of anodized Ta2O5. The findings show that anodized Ta2O5 is reliable to be employed as gas sensor, photocatalysis, pH sensor, biomedical materials and humidity sensor due to its superior properties to produce high sensitivity device and increase the efficiency. In this review, a general overview of anodized Ta2O5 is presented which focuses on its fundamental properties, method of synthesis anodized Ta2O5, anodization parameter optimization, and recent applications in chemical and biological area, along with a discussion on future research directions relevant to this material. It is hoped that by synthesising nanostructures via anodization, the sensing performance will improve and Ta2O5 will be proven as a trustworthy metal oxide material for sensing applications.